2022
DOI: 10.1002/jcla.24373
|View full text |Cite
|
Sign up to set email alerts
|

Plasma growth differentiation factor‐15 in patients with “lone” atrial fibrillation

Abstract: Growth differentiation factor-15 (GDF-15) is a member of the transforming growth factor β superfamily. 1 Its expression is correlated with diverse stimuli, including oxidation, inflammation, hypoxia, tissue injuries, and so on. 2,3 Cardiovascular disease is also closely related to GDF-15 production. 4 As a popular cardiovascular disease, atrial fibrillation (AF) poses high burden globally. Moreover, about five million new cases are diagnosed annually. Thus, substantial efforts are made toward the mechanism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…It has been reported that plasma and atrial tissue expression of GDF-15 are higher in patients with AF than in those with sinus rhythm. 31 GDF-15 is also related to clinical outcomes, including mortality, major bleeding, and stroke, in patients with AF. 14 …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that plasma and atrial tissue expression of GDF-15 are higher in patients with AF than in those with sinus rhythm. 31 GDF-15 is also related to clinical outcomes, including mortality, major bleeding, and stroke, in patients with AF. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocyte expression of GDF15 was highly induced by ischemia and reperfusion injury and was associated with cardiac fibrosis after inflammation due to AMI and HF. Elevated concentrations of GDF15 predicted newly onset atrial fibrillation [79], cardiac thrombosis [80], cardioembolic stroke, and AMI, but not HF and non-ischemic cardiomyopathy [81]. GDF15 is considered a promising biomarker or a potential therapeutic target for the management of HF; however, models based on GDF15 have not yet been validated and are frequently based on retrospective investigations.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%